RETRACTED - Characterization and Mode-Locking of Erbium-Doped Fiber Laser for Ultra-Short Pulse Generation (Patan Prospective Journal, 2023)
Retraction NoticeOn 4th December 2023 this article was retracted due to numerous errors in the paper. Two of the authors were included without their permission and therefore have been removed.